Embedded software development for safety-critical systems - Hobbs, Chris (CRC Press, 2020)
This is a book about the development of dependable, embedded software. It is for systems designers, implementers, and verifiers who are experienced in general embedded software development, but who are now facing the prospect of delivering a software-based system for a safety-critical application. It is aimed at those creating a product that must satisfy one or more of the international standards relating to safety-critical applications, including IEC 61508, ISO 26262, EN 50128, EN 50657, IEC 62304, or related standards. Of the first edition, Stephen Thomas, PE, Founder and Editor of FunctionalSafetyEngineer.com said, "I highly recommend Mr. Hobbs' book."